Late Campanian-Maastrichtian Kamptnerius magnificus acme in the South Atlantic section of the Southern Ocean, ODP Holes 690C and 700B - Guerra, Rodrigo M. (2016)
Coccolithophores are organisms with distribution largely controlled by temperature and availability of nutrients. For extinct calcareous nannofossils there are some uncertainties in assigning ecological preferences of taxa, however sometimes species occurrences exhibits striking high abundances showing clear preferences for certain environment, the so-called acme events. During quantitative analyses on samples from the South Atlantic section of the Southern Ocean (Holes 690C and 700B) a notable Kamptnerius magnificus acme was documented. This is the first time that such bioevent is described for the South Atlantic Ocean. Preliminary analysis indicates that this event probably is related to the cooling in sea-surface temperatures during the Late Campanian-Maastrichtian.